Sprouty2 acts at the Cbl/CIN85 interface to inhibit epidermal growth factor receptor downregulation - Haglund, Kaisa (2005)
The ubiquitin ligase Cbl mediates ubiquitination of activated receptor tyrosine kinases (RTKs) and interacts with endocytic scaffold complexes, including CIN85/endophilins, to facilitate RTK endocytosis and degradation. Several mechanisms regulate the functions of Cbl to ensure the fine-tuning of RTK signalling and cellular homeostasis. One regulatory mechanism involves the binding of Cbl to Sprouty2, which sequesters Cbl away from activated epidermal growth factor receptors (EGFRs). Here, we show that Sprouty2 associates with CIN85 and acts at the interface between Cbl and CIN85 to inhibit EGFR downregulation. The CIN85 SH3 domains A and C bind specifically to proline–arginine motifs present in Sprouty2. Intact association between Sprouty2, Cbl and CIN85 is required for inhibition of EGFR endocytosis as well as EGF-induced differentiation of PC12 cells. Moreover, Sprouty4, which lacks CIN85-binding sites, does not inhibit EGFR downregulation, providing a molecular explanation for functional differences between Sprouty isoforms. Sprouty2 therefore acts as an inducible inhibitor of EGFR downregulation by targeting both the Cbl and CIN85 pathways.